Does the investment climate matter? : microeconomic foundations of growth in Latin America - Fajnzylber, Pablo; Guasch, J. Luis; Lopez, J. Humberto (Latin American development forum., 2009)
Although the Latin American region's growth rates are at a three decade high, they have been historically disappointing in relative terms, which cannot be dissociated from the microeconomic environment in which firms operate. Policy makers may need to complement their focus on macroeconomic stability with an increased emphasis on microeconomic reforms. By providing empirical evidence linking actual firm performance to shortcomings in Latin America's investment climate, the book discusses policies that could have a significant impact on firm productivity by improving the environment in which fi.